2015
DOI: 10.1177/2040622315586970
|View full text |Cite
|
Sign up to set email alerts
|

Vedolizumab: an α4β7 integrin antagonist for ulcerative colitis and Crohn’s disease

Abstract: Ulcerative colitis (UC) and Crohn's disease (CD) are chronic, relapsing inflammatory bowel diseases associated with significant morbidity. Conventional therapies for these diseases include corticosteroids, aminosalicylates, immunomodulators, and monoclonal antibodies. Over the years tumor necrosis factor (TNF)-α antagonists alone or in combination with other therapies have emerged as the cornerstone of treatment for induction and maintenance of remission of moderate to severe UC and CD. Unfortunately, some pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 33 publications
0
26
0
1
Order By: Relevance
“…Serious infections were identified in 5.5% of vedolizumab therapy patients compared with 3.0% of the patients under placebo. No cases of PML or malignancies were identified [ 28 - 31 ].…”
Section: Integrin Antagonistsmentioning
confidence: 99%
“…Serious infections were identified in 5.5% of vedolizumab therapy patients compared with 3.0% of the patients under placebo. No cases of PML or malignancies were identified [ 28 - 31 ].…”
Section: Integrin Antagonistsmentioning
confidence: 99%
“…151,167 A recently published study by Colombel et al observed the long-term safety of VDZ across six trials, 2,830 patients with 4,811 person-years of follow-up, and in this population, if treated with NAT, six to seven cases of PML would have been expected. Again, when compared to placebo, there was no increased risk of any infection.…”
Section: Biologicsmentioning
confidence: 96%
“…150 Anti-integrin monoclonal antibodies bind to the integrin, preventing its interaction with the inflamed mucosa, hence reducing the migration of effector lymphocytes into gut tissue, and reducing the inflammatory process. 151 …”
Section: Biologicsmentioning
confidence: 99%
“…As the most common adverse effects of vedolizumab were reported: nasopharyngitis, headache, arthralgia, and nausea. Longer-term safety trials are needed but based on evidence to date, there is no evidence of a higher odds of serious infections from the newly available biologic therapies, such as vedolizumab, compared to the anti-TNF agents (5) and also the progressive multifocal leukoencephalopathy (PML) associated with vedolizumab has not been reported (6).…”
Section: Introductionmentioning
confidence: 99%